Tax Guide 2014-2015 - Sinclair, Walter; Lipkin, Barry; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
The 43rd annual edition of the leading guide to taxation in Britain. This practical and user-friendly guide is a bestseller with students, professionals, accountants and private individuals, explaining in simple terms how the UK tax system works and how best to minimise tax liabilities.
Keywords: Business; Accounting; Bookkeeping; Tax accounting; Tax laws; Small business; Finance, Public; Economics; Management science; Business and Management; Small Business; Financial Accounting; Business Taxation/Tax Law; Accounting/Auditing.; Economics, general; Public Finance